POWER AND DESPAIR THROUGH THE LENS OF INTERPERSONAL METAFUNCTION: A MOOD AND MODALITY ANALYSIS OF DENIS VILLENEUVE’S PRISONERS (2013) - Sufina Zahra Rambe; Uswatun Hasanah Lubis; Fathia Naziva (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
This research aims to analyze mood and modality in the dialogues and to explore how interpersonal metafunction reflects power and despair. The audience of Prisoners movie often focused on the father-daughter relationship between Keller and Anna which overlooks the significance of character interactions in constructing meaning. This study applies a descriptive qualitative method using selected scenes from the movie script focusing on Keller and Loki. It applies Halliday’s Systemic Functional Linguistics, particularly the interpersonal metafunction, along with Rotter’s Locus of Control theory to examine how power and despair are constructed by linguistic choices. The findings show that obligation is the most dominant type of modality, with Keller’s dialogue highly dominated by obligation, reflecting his tendency to control situations. Keller also shows a dominance of internal Locus of Control, indicating his refusal to be passive, while Loki demonstrates a balance between internal and external control. In terms of mood, Keller frequently uses declarative and imperative sentences, while Loki often uses interrogative forms